Intestinal inflammation and the diet: Is food friend or foe? - Megna, Bryant W (World J Gastrointest Surg, 2016)
Inflammatory bowel disease (IBD) is a chronic intestinal illness of autoimmune origin affecting millions across the globe. The most common subtypes include ulcerative colitis (UC) and Crohn’s disease. While many medical treatments for IBD exist, none come without the risk of significant immunosuppression and in general do not have benign side effect profiles. Surgical intervention exists only as radical resection for medically refractory UC. There exists a dire need for novel treatments that target the inherent pathophysiologic disturbances of IBD, rather than global immune suppression. One avenue of investigation that could provide such an agent is the interaction between certain dietary elements and the aryl hydrocarbon receptor (AHR). The AHR is a cytosolic transcription factor with a rich history in environmental toxicant handling, however, recently a role has emerged for the AHR as a modulator of the gastrointestinal immune system. Studies have come to elucidate these effects to include the enhancement of T(h) cell subset differentiation, interactions between enteric flora and the luminal wall, and modulation of inflammatory interleukin and cytokine signaling. This review highlights advancements in our understanding of AHR activity in the digestive tract and how this stimulation may be wrought by certain dietary “micronutriceuticals”, namely indole-3-carbinol (I3C) and its derivatives. Greater clarity surrounding these dynamics could lead to a novel diet-derived agonist of the AHR which is not only non-toxic, but also efficacious in the amelioration of clinical IBD.